Perspectivas de los biocombustibles en Colombia (2015)
Colombia is beginning in bioenergy and requires policies and infrastructure for the production of biofuels. In recent years, biofuels come forward supported by the adoption of law decrees that allow the introduction of biofuels, at first mixed with fossil fuels such as gasoline and diésel instance. This article “Topic Review” presents the beginning and development of biofuels in Colombia, as well as the current production situation, companies and organizations leading this project, in order to adopt a renewable and sustainable energy. In analyzing this issue on biofuels in Colombia a clear beginning to the independence of fossil fuels, with the premise of a sustainable energy matrix to ensure industry growth, social development and environmental protection is noted. On the other hand the trend is observed worldwide to adopting biofuels mainly oil-dependent countries, with South American countries like Brazil, Colombia and Argentina the champions in these proposals. Colombia in turn presented in this field of biofuels available land resources, labor, internal consumption and production policies; but with the existence of difficulties in social inequality, internal conflicts, monopolies and political barriers that could prevent private and foreign investment.